FOREIGN ECONOMIC SECURITY OF UKRAINE IN THE CONTEXT OF NATIONAL ECONOMY OPENNESS - Dernova I. А.; Ivanova I. V.; Borovyk T. M.; Rudenko А. Y. (Scientific Journal of Pedagogy and Economics, 2021)
Under the conditions of increasing intensity of globalization and integration processes, issues of foreign economic security are of special importance. The level of the country’s involvement in the world economy is considered as a basic indicator of the economic system development. Provided that comparative advantages are effectively applied, openness serves as a factor in the development of economy and allows using advanced world technologies and financial resources. The possibility of growth for the national economy as a whole as well as wellbeing of each subject of the economic system in particular largely depend on the structure and volume of foreign trade. The study analyses the key approaches of various scientists to the interpretation of the economic category called foreign economic security, assesses the degree of foreign trade openness of the national economy based on such indicators as export quota (characterizing the level of export dependence), import quota (characterizing the level of import dependence) and foreign economic quota (which is an indicator of economy’s openness). To assess the level of foreign economic security, security indicators have been considered in accordance with the Methodology for Calculating Economic Security Level. For each indicator, according to the threshold values, the state of security has been determined and an assessment of its level change during 2011-2018 has been carried out. Since the indicators characterizing foreign trade sphere are in a critical state, attention is paid to the analysis of foreign trade indicators of Ukraine. The list of problems of a systemic nature has been worked out, the main threats to foreign economic security have been identified and priority directions for its strengthening have been offered. General recommendations for creating favourable conditions for economic development in foreign trade have also been provided.